Overexpression of an EIN3-binding F-box protein2-like gene caused elongated fruit shape and delayed fruit development and ripening in tomato. (July 2018) - Guo, Xiaokun; Zhang, Yong; Tu, Yun; Wang, Yongzhong; Cheng, Wenjing; Yang, Yingwu
Highlights: A novel tomato F-box protein, SlEBF2-like, is greater similarity to SlEBF2. SlEBF2-like belongs EBF subfamily involved in ethylene signaling pathway. SlEBF2-like is nuclear-localized and positively regulated by ethylene. SlEBF2-like overexpression elongated fruit shape and altered fruit ripening pattern. SlEBF2-like overexpression delayed fruit development and ripening. Abstract: Ethylene signaling converges on the ETHYLENE-INSENSITIVE3 (EIN3)/EIN3-like (EIL) transcription factors to regulate a wide range of developmental processes in plants. EBF1/2 (EIN3-binding F-box protein 1 and 2) negatively regulate the ethylene signaling pathway by mediating the degradation of EIN3/EIL proteins. We uncovered previously that SlEBF1 and SlEBF2 are involved in ethylene response, plant senescence, and fruit ripening in tomato. The present study reports on the identification of a novel tomato F-box gene, designated as SlEBF2-like due that its encoded protein is greater similarity to SlEBF2. The SlEBF2-like promoter region contains three ethylene-response elements (EREs). SlEBF2-like is upregulated by ethylene and downregulated by ethylene inhibitors in tomato seedlings. It is dynamically expressed in flowers during bud-to-anthesis and anthesis-to-post-anthesis transitions, and at the onset of fruit ripening, suggesting its role in these situations where ethylene is required for flower opening and fruit ripening. SlEBF2-like overexpression leaded to fruit elongation, caused ripening and color change to start from fruit bottom and expand gradually to the pedicel, and strongly delayed fruit development and ripening in tomato. Our study indicates that the novel EBF gene, SlEBF2-like, is involved in fruit development and ripening via regulating the ethylene response in tomato.